PENGEMBANGAN E-MODUL MENGGUNAKAN VIDEO BERBASIS WONDERSHARE FILMORA MATERI TEKS EKSPLANASI UNTUK MENINGKATKAN HASIL BELAJAR - Jaja Sudarjat,; Nanda Dwi Lestari,; Raden Teti Rostikawati, (Journal of Innovation Research and Knowledge, 2025)
The purpose of this study is to develop an e-module using Wondershare Filmora- based video explanatory text material, so that it is feasible to be tested and effective to be able to improve students' learning outcomes. This research method uses the Research and Development (R&D) method with the ADDIE (analysis, design, development, implementation and evaluation) development model. This research involved 30 students and in the process of validation and trial of the e- modules that have been developed. Validation was carried out by validators, namely material experts, teacher subject matter experts, linguists, and media experts, with the validation results of 92% of the subject matter experts, 100% of teacher subject matter experts, 92% of linguists, and media experts of 97% with an average result of 95.25% which was included in the "Very Feasible" criteria. It was strengthened by the results of student respondents of 100% and teacher responses of 100% included in the category of "Very Good". Similarly, the average result of the N-Gain value is 0.85 in the category "Effective". From the results of the research, it can be concluded that the e-module uses Wondershare Filmora- based videos that were developed effectively and practically to be used in measuring students' understanding of explanatory text material